Exploring the anti-cancer potential of methanolic extract from Simarouba glauca: Induction of apoptosis and growth inhibition in lung cancer cells - K.B. Gurudhathan; Jeelani Peerzada; Arul Prakesh; M.S. Mohamed Jaabir (Oral Oncology Reports, 2023)
The causes behind lung cancer etiology remain unknown, and treatment failure is often caused by medication resistance, recurrence, and metastasis. Clinical development of novel therapeutic molecules to overcome drug resistance remains a problem. The purpose of this study was to evaluate the potential of Simarouba glauca triterpenoids among two different plant extracts (leaf extract and bark extract) in two human cell lines: lung adenocarcinoma (A549) and normal lung (L132) cell lines using four different solvents. The concentration yield of methanolic bark extract and leaf extracts was found to be higher compared to the other solvents using the Soxhlet method of extraction. Phytochemical analysis using Liberman-Burchard's test conducted confirmed the presence of triterpenoids in Methanolic extract from barks of Simarouba glauca. Comparative cytotoxicity potential among the extracts from bark and leaves, bark extracts showed an IC50 and LD50 as 350 μg/mL and 300 μg/mL respectively on the A549 cell lines of lung carcinoma. Cell cycle analysis using Methanolic bark extracts in comparison to the leaf extracts showed the arrest of the proliferation of A549 cells at the G0/G1 stage with a significant increase in cells at a level of 42.33%, 23.93%–23.47%, 17.96% respectively. Increased Reactive Oxygen Species (ROS) levels in the A549 cells in 1 h treated with bark extract and leaf extract than in the untreated cells. The methanolic extract from both the bark and leaves was found to be the most potent presenting potential arrest of cell cycle, reactive oxygen species generation and apoptosis. In summary, our study has found that the S. glauca-based plant extract has the anticancer potential by triggering apoptosis.